Determination and Analysis of Obstacles of Innovation in Malaysian Food Processing SMEs - Suziyana, Mat Dahan; Mohd Yusof, Taib; Ahmad Nazif, Noor Kamar; Khairul Anwar, Hamzah (IJEIT, 2014)
This paper discusses the innovation obstacles among Small and Medium Enterprises (SMEs). It aims to identify the main barriers of innovation in Malaysian food processing SMEs and seeking the best approach to overcome each of the barriers of innovation in Malaysian food processing SMEs. 163 sets of questionnaires were distributed among managers or owners of the food processing SMEs around Selangor, Malaysia and 77 responses had been collected and recorded. By using Statistical Package for the Social Sciences (SPSS), the result obtained by finding the mean value for each of the item assessed. From all the four barriers of innovation that had been studied like financial barrier, market barrier, organizational culture barrier and lack of information and skilled personnel barrier, it can be concluded that the financial barrier is the main barrier of innovation in Malaysian food processing SMEs. The financial barriers can be overcome by an easy financial loan application by the government for new machine or new equipment purchasing for SMEs. To eliminate the market factor barrier, the fear of failure need to be eliminated and be open minded. Next, the company has to give detail explanations about innovation to the employees to overcome the organizational culture barrier. Lastly to overcome the lack of information and skilled personnel barrier, more training, skills and knowledge program and workshops related to innovation for SMEs need to be held by government agencies. Both research objectives have been achieved and the findings are mainly benefit the SMEs practitioners and also related government agencies in restructuring the strategies towards more efficient innovation adoption and implementation.